2008
DOI: 10.1073/pnas.0709657105
|View full text |Cite
|
Sign up to set email alerts
|

Saturation mutagenesis of putative catalytic residues of benzoylformate decarboxylase provides a challenge to the accepted mechanism

Abstract: Benzoylformate decarboxylase from Pseudomonas putida (PpBFDC) is a thiamin diphosphate-dependent enzyme that carries out the nonoxidative decarboxylation of aromatic 2-keto acids. The x-ray structure of PpBFDC suggested that Ser-26, His-70, and His-281 would play important roles in its catalytic mechanism, and the S26A, H70A, and H281A variants all exhibited greatly impaired catalytic activity. Based on stopped-flow studies with the alanine mutants, it was proposed that the histidine residues acted as acid-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 27 publications
5
77
1
Order By: Relevance
“…More recently, McLeish and coworkers have been carrying out saturation mutagenesis experiments [17] probing the function of two active center histidine residues (His70 and His281) on benzoylformate decarboxylase (BFDC), long believed to participate in acid-base reactions [18]. Surprisingly, their results indicated that hydrophobic residues could replace the His281 with little penalty, and even with His70 there was only a 70-fold penalty on k cat /K m .…”
Section: Introductionmentioning
confidence: 96%
“…More recently, McLeish and coworkers have been carrying out saturation mutagenesis experiments [17] probing the function of two active center histidine residues (His70 and His281) on benzoylformate decarboxylase (BFDC), long believed to participate in acid-base reactions [18]. Surprisingly, their results indicated that hydrophobic residues could replace the His281 with little penalty, and even with His70 there was only a 70-fold penalty on k cat /K m .…”
Section: Introductionmentioning
confidence: 96%
“…This was in keeping with the proposed role of His281 in catalysis [10]. However, in a later saturation mutagenesis study, it was found that several residues incapable of acting as a general acid could replace His281 with only a modest decrease in activity [13]. In particular, the H281Y variant displayed only an 84-fold decrease in k cat /K m and this was largely due to a 46-fold decrease in k cat value [13].…”
Section: Analysis Of the Teedmentioning
confidence: 72%
“…Successful mutagenesis was indicated by the presence of new XmaI and XmnI restriction sites for the Y281H and I466A variants, respectively. The mutations, and the absence of extraneous The PpBFDC H281Y and A460I variants were available from previous studies [12,13]. The H281Y/A460I double mutant was prepared by PCR mutagenesis on pET24PpBFDC_H281Y-His [13] followed by screening for loss of a BanI restriction site.…”
Section: Cloning and Construction Of Expression Vectorsmentioning
confidence: 99%
See 2 more Smart Citations